Fast-forward : key issues in modernizing the U.S. freight transportation system for future economic growth - Hillestad, R. J. (Richard John), 1942- (RAND Corp., 2009)
Efficient movement of freight within the United States and across its borders is a critical enabler of future U.S. economic growth. The authors provide an overview of the freight-transportation system and the problems it faces, concluding with a discussion of key system-modernization issues, including increasing capacity, making the system less vulnerable to disruption, addressing environmental concerns, and building support for funding.